Annual Plan 1980-81 Planning Department Punjab - Planning Commission (Planning Commission, 1980)
The draft Annual Plan 1980-81 was a part of and in conformity with the sixth Five Year Plan 1978-83. The Planning Commission has now decided that the Annual Plan 1980-81 shall form the base year for the new Sixth Five Year plan which will cover the period 1980-81 to 1984-85. It has been decided that Annual Plan 1980-81 of the Punjab State should be reoriented in accordance with the objectives and strategy of the new Sixth Five Year Plan and it should be dovetailed to the new Sixth Five Year Plan to be finalised by September, 1980.
Planning Department Punjab